(untitled) (LEARNing Landscapes, 2018)
Schools are relational places where the meeting of characters, stories, experiences, and understandings move about each other daily. In the busyness of school life, time is usually not taken to listen to, observe, and share the stories and experiences of others; to shift from a condition of moving about to a place where we are walking alongside. The narratives provided here are reflections on my experiences of my time in school as student, teacher, and administrator. I write these to honor my sister’s voice and the many voices that fueled my hope as a teacher and teacher educator for teaching and learning.